2019
DOI: 10.1186/s12886-019-1198-7
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the development and implementation of a patient-reported outcome and experience measure (POEM) in an Australian glaucoma practice

Abstract: Background A patient’s perception of how their glaucoma is managed will influence both adherence to their medication and outcome measures such as quality of life. Methods Prospective consecutive study using a Glaucoma Patient-reported Outcome and Experience Measure (POEM) modified for an Australian ophthalmic private clinical practice setting. The Australian Glaucoma POEM consists of eight items related to the patient’s understanding of the diagnosis and management, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 19 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…The patient-reported outcome and experience measure (POEM) is a validated eight-item questionnaire for use in glaucoma [1,2]. The questionnaire addresses aspects of outcome (acceptability of treatment, fear of blindness, impact on daily life) and aspects of experience (safety, understanding, organization of care).…”
Section: To the Editormentioning
confidence: 99%
“…The patient-reported outcome and experience measure (POEM) is a validated eight-item questionnaire for use in glaucoma [1,2]. The questionnaire addresses aspects of outcome (acceptability of treatment, fear of blindness, impact on daily life) and aspects of experience (safety, understanding, organization of care).…”
Section: To the Editormentioning
confidence: 99%
“…However, the validity and reliability of such a tool needed further research. The use of a glaucoma POEM adapted for a private clinic case mix has been recently described by Fraenkel et al [16] This study demonstrated the feasibility of employing a POEM in a clinical care setting and successfully captured the concerns of a practice's glaucoma cohort with the view to use the obtained information to enhance the quality of glaucoma care delivered.…”
Section: Discussionmentioning
confidence: 86%
“…Unlike other tools that required trained personnel and consist of lengthy questionnaires, this POEM has been optimized for routine clinical application in wet MD patients. [15][16][17][18] It is extremely important to move from the patient being the "object" of patientcentered care to being the "subject." The quantitative data output obtained from the modified POEM, will aid in health care and research agendas being realigned according to the patients' experiences and priorities.…”
Section: Discussionmentioning
confidence: 99%
“… 83 85 Such approaches have been shown to be psychometrically valid and could be useful along with hybrid methods that try to capture a measure of a person’s so-called patient-reported outcome and experience (POEM). 86 …”
Section: Discussionmentioning
confidence: 99%